2002
DOI: 10.1130/0091-7613(2002)030<0071:nrsfot>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Nile River sediment fluctuations over the past 7000 yr and their key role in sapropel development

Abstract: The provenance pattern of Nile River sediments can be used as a proxy for paleoclimatic changes in East Africa. The 87 Sr/ 86 Sr ratios are particularly appropriate for such provenance investigations, because the White Nile drains predominantly crystalline basement rocks, whereas the Blue Nile and Atbara flow off the Ethiopian Highlands, which consist of Tertiary volcanic rocks. A high-resolution profile of 87 Sr/ 86 Sr and Ti/Al ratios from a well-dated core in the Nile Delta shows a close correspondence with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
129
0
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 228 publications
(143 citation statements)
references
References 24 publications
5
129
0
9
Order By: Relevance
“…Estimated northernmost positions of the ITCZ during the AHP and present day adapted from Junginger et al (2014). a Gulf of Aden sediment core (Tierney and deMenocal 2013), b Indian Ocean sediment core (Bard et al 1997), c Paleolake Suguta (Garcin et al 2009;Junginger et al 2014), d Lake Chew Bahir (Foerster et al 2012), e Lake Ashenge (Marshall et al 2009), f Lake Tilo (Lamb et al 2000), g Lakes Ziway and Shala (Gillespie et al 1983), h Lake Tana (Costa et al 2014;Marshall et al 2011), i Lake Abbe (Gasse and Van Campo 1994), j Blue Nile sediment sources (Krom et al 2002) and k Lake Hayq (Lamb et al 2007) (image in full color online) and a permanent lowstand at Lake Abbe (a.k.a. Abhé; Fig.…”
Section: Paleoclimate Of Adjacent Basinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimated northernmost positions of the ITCZ during the AHP and present day adapted from Junginger et al (2014). a Gulf of Aden sediment core (Tierney and deMenocal 2013), b Indian Ocean sediment core (Bard et al 1997), c Paleolake Suguta (Garcin et al 2009;Junginger et al 2014), d Lake Chew Bahir (Foerster et al 2012), e Lake Ashenge (Marshall et al 2009), f Lake Tilo (Lamb et al 2000), g Lakes Ziway and Shala (Gillespie et al 1983), h Lake Tana (Costa et al 2014;Marshall et al 2011), i Lake Abbe (Gasse and Van Campo 1994), j Blue Nile sediment sources (Krom et al 2002) and k Lake Hayq (Lamb et al 2007) (image in full color online) and a permanent lowstand at Lake Abbe (a.k.a. Abhé; Fig.…”
Section: Paleoclimate Of Adjacent Basinsmentioning
confidence: 99%
“…High sedimentation rates and low flows in the Blue Nile ( Fig. 1(j)) are documented from 5,650 to 4,750 and 2,050 to 1,000 years BP (Krom et al 2002). An analysis of oxygen and carbon isotopes in carbonates and diatom assemblages from a sediment core from Lake Hayq ( Fig.…”
Section: Paleoclimate Of Adjacent Basinsmentioning
confidence: 99%
“…Well dated records for the dynamics of the River Nile in Northern Sudan and the Nile Delta now exist (e.g., Krom et al, 2002;Kuper & Kröpelin, 2006;Williams et al, 2010;Macklin et al, 2013), however correlation of these data with the data reported here remains problematic since we do not have direct dates on the sediments in which our data were observed. In the past, sediments indicative of past lake levels were correlated with archaeological materials and regional to global palaeoenvironmental records but as we suggest in this paper, these associations were not correctly interpreted due to the types of absolute dates that were obtained (i.e., from archaeological not lacustrine deposits).…”
Section: Discussionmentioning
confidence: 67%
“…Ces considérations ont motivé plusieurs études miné-ralogiques, chimiques et géochimiques portant sur la contribution relative des deux sources (équatoriale et éthiopienne) au cours du temps. Foucault & Stanley (1989) Sr dans les sédiments du Nil (Box et al, 2011 ;Krom et al, 2002 ;Revel et al, 2010 ;Stanley et al, 2003). L'analyse isotopique du strontium a permis de retracer l'évolution de la quantité de précipitations en Éthiopie entre 6000 et 1500 BP (Krom et al, 2002 ;Stanley et al, 2003).…”
Section: -Introductionunclassified
“…Foucault & Stanley (1989) Sr dans les sédiments du Nil (Box et al, 2011 ;Krom et al, 2002 ;Revel et al, 2010 ;Stanley et al, 2003). L'analyse isotopique du strontium a permis de retracer l'évolution de la quantité de précipitations en Éthiopie entre 6000 et 1500 BP (Krom et al, 2002 ;Stanley et al, 2003). Elle présente cependant plusieurs limites : d'une part, l'intégration du signal par le couvert forestier implique un décalage temporel entre l'augmentation des précipitations et la réduction de la charge sédimentaire ; d'autre part, le (Iacumin et al, 1996).…”
Section: -Introductionunclassified